2020
DOI: 10.1128/aem.00367-20
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Acidocin 4356 Combats Pseudomonas aeruginosa through Membrane Perturbation and Virulence Attenuation: Experimental Results Confirm Molecular Dynamics Simulation

Abstract: A longstanding awareness in generating resistance to common antimicrobial therapies by Gram-negative bacteria has made them a major threat to global health. The application of antimicrobial peptides as a therapeutic agent would be a great opportunity to combat bacterial diseases. Here, we introduce a new antimicrobial peptide (∼8.3 kDa) from probiotic strain Lactobacillus acidophilus ATCC 4356, designated acidocin 4356 (ACD). This multifunctional peptide exerts its anti-infective ability against Pseudomonas ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The potential effects of CFS on cell morphology and structure of E. coli ATCC25922 and S. aureus ATCC6538 were determined by SEM and TEM [ 56 , 57 ]. Briefly, bacterial dilutions (10 7 CFU/mL) in LB medium were supplemented with 1/2 MIC of CFS and incubated for 10 h at 37 °C by shaking.…”
Section: Methodsmentioning
confidence: 99%
“…The potential effects of CFS on cell morphology and structure of E. coli ATCC25922 and S. aureus ATCC6538 were determined by SEM and TEM [ 56 , 57 ]. Briefly, bacterial dilutions (10 7 CFU/mL) in LB medium were supplemented with 1/2 MIC of CFS and incubated for 10 h at 37 °C by shaking.…”
Section: Methodsmentioning
confidence: 99%
“…37 Outro exemplo de metabólito produzido por espécies de Lactobacillus, que apresenta ação antimicrobiana contra P. aeruginosa, é a acidocina 4356, um peptídeo antimicrobiano produzido pela espécie L. acidophilus, o qual apresenta capacidade de inibição dos fatores de virulências, morte do micro-organismo e degradação de biofilmes. 38 Lactobacillus são investigados em conjunto com diferentes tipos de antibióticos. Estudos já demonstram que espécies de Lactobacillus associadas a antibióticos favoreceram o tratamento contra a colonização da microbiota intestinal de bactérias multirresistentes, como, por exemplo, P. aeruginosa.…”
Section: Lactobacillus Spp -Potencial Terapêuticounclassified
“…Compared with the control group, the peptide-treated mouse lung slices exhibited the decreased recruitment of macrophages and lung cells, as well as a reduction in epithelial hyperplasia and structural degeneration. Mechanism of action experiments revealed that ACD not only enhanced bacterial membrane perturbation, but also reduced the production of P. aeruginosa virulence factors, such as pyoverdine siderophore, pyocyanin toxin, secretory protease, and elastase enzyme ( Modiri et al, 2020 ). Moreover, it had a low hemolytic activity of less than 20% on human erythrocytes at a concentration of 400 μg/mL, indicating its potential as a promising therapeutic compound.…”
Section: Anti- Pseudomonas Aeruginosa Activity Of ...mentioning
confidence: 99%
“…In addition to their ability to bind to bacterial membrane lipids and enhance membrane permeability, Lynronne-1 In addition to rumen microbiome, bacteriocins produced by lactic acid bacteria (LAB) had been extensively studied due to their safety and utility. Acidocin 4356 (ACD) is a novel bacteriocin with a size of 8.3 kDa, which was isolated from Lactobacillus acidophilus ATCC 4356 (Modiri et al, 2020). ACD had antimicrobial activity against both E. coli and P. aeruginosa, causing 35 and 80% inhibition of their growth at the same concentration.…”
Section: Amps From Microorganismsmentioning
confidence: 99%